Green Value Chain Costs and Their Role in Achieving Sustainable Competitive Advantage - Hasan, Mustafa Saeed; Sorour, Manal Jabbar (Journal of Ecohumanism, 2024)
Iraqi companies suffer from a significant waste of resources and an increase in the costs of operations and materials for producing the 2-ton window air conditioner. The reason is that these Iraqi companies did not apply green technologies in their activities and operations. The research aims to develop a 2-ton window air conditioner through the use of green value chain technology, focusing on the activities of green research and development, and green design through (replacement, redesign) to achieve the dimensions of sustainable competitive advantage represented by (cost, quality, flexibility, and concern for the environment). . In his study, the researcher relied on the company’s data for the year 2023, in addition to repeatedly visiting the factory and conducting personal interviews with relevant parties. The researchers reached several conclusions, including that redesigning the heat exchanger from 4 rows to 3 rows will lead to reducing costs by an amount of 20,306 dinars for materials and production processes and increasing the efficiency of cooling performance, in addition to reducing the time of production operations from 45 minutes to 35 minutes, and replacing the gas is unnecessary. Environmentally friendly using environmentally friendly gas will lead to increased performance efficiency, reduced costs, and preservation of the environment due to the inability of environmentally friendly gas to deplete the ozone layer.